Pengaruh Leverage dan Investmen Opportunity Set Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Property 2021-2023 Yang Ada di Bursa Efek Indonesia) - Irawan, Septian Bambang (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the effect of Leverage, Investment Opportunity Set on Firm Value with a case study on Property Companies from 2021 to 2023. The research method used is descriptive quantitative. The tests carried out include the chow test, hausman test, normality test, multicolonierity test, coefficient of determination test, f test, t test. The results showed that in testing the Leverage Hypothesis and Investment Opportunity Set had no effect on Firm Value with a Leverage coefficient value of 0.015318 and a significance value of 0.8712> 0.05 and an IOS coefficient value of 0.030693 and a significance value of 0.9038> 0.05